Activated protein C induces suppression and regression of choroidal neovascularization– A murine model. (September 2019) - Livnat, Tami; Weinberger, Yehonatan; Budnik, Ivan; Deitch, Iris; Dahbash, Mor; Sella, Ruti; Dardik, Rima; Kenet, Gili; Nisgav, Yael; Weinberger, Dov
Abstract: Activated protein C (APC) exerts diverse cell signaling pathways which results in multiple distinct cytoprotective actions. These include anti-apoptotic and anti-inflammatory activities and stabilization of endothelial and epithelial barriers. We studied the ability of APC to inhibit the leakage and the growth of newly formed as well as pre-existing choroidal neovascularization (CNV) and examined the ability of APC to stabilize the Retinal Pigmented Epithelium (RPE). We explored the contribution of Tie2 receptor to the protective effects of APC. CNV was induced by laser photocoagulation in C57BL/6J mice. APC was injected intravitreally immediately or 7 days after CNV induction. Neovascularization was evaluated on RPE-choroidal flatmounts using FITC-dextran perfusion and CD31 immunofluorescence. CNV leakage was measured by fluorescein angiography (FA). The ability of APC to stabilize the RPE barrier was evaluated in-vitro by dextran permeability and zonula occludens 1 (ZO1) immunostaining. Tie2 blocking was induced in-vivo by intraperitoneal injection of Tie2 kinase inhibitor and in-vitro by incubation with anti Tie2 antibodies. APC treatment dramatically inhibited the generation of newly formed CNV leakage sites and reversed leakage in 85% of the pre-existing CNV leaking sites. In RPE cell culture, APC induced translocation of ZO1 to the cell membrane, accompanied by reduction in permeability of the monolayer. Inhibition of Tie2 significantly decreased APC protective activities in both the mouse model and the RPE cell culture. Our results show that APC treatment significantly inhibits the leakage and growth of newly formed, as well as pre-existing CNV, and its protective activities are partially mediated via the Tie2 receptor. The data suggest that APC should be further investigated as a possible effective treatment for CNV. Highlights: APC inhibits the growth of newly formed and pre-existing CNV in a mouse model. APC inhibits and reverses leakage from new and pre-existing CNV, respectively. APC tightens RPE monolayer in vitro and translocates ZO1 to cell membrane. APC protective activities are partially mediated via the Tie2 receptor.